What students can learn from Fibonacci´s error in solving "The lion in the pit" problem - Josip Slisko (Universidad Distrital Francisco José de Caldas, 2020)
This initial study presents the results of the classroom implementation of a learning sequence derived from Fibonacci's error in solving 'The lion in the pit' problem. The study was carried out with 35 physics students in a general first-semester course 'Development of complex-thinking skills'. The learning sequence was implemented as a paper-and-pencil activity in personal and group modes. The most important results are the following: (a) Students were able to provide an acceptable procedure about how Fibonacci might get the wrong answer, (b) students can argue why that answer is wrong, (c) some students' solutions presented good conceptual and procedural clarity, frequently missed in historic literature, and (d) students grasped the importance of knowing about errors made by famous mathematicians in two connected aspects: mathematics is a human activity prone to errors and, consequently, fear of errors shouldn't be an obstacle in learning of school mathematics.